Theoretical concepts for building Smart cities - Nikolov, Nikolay; Pavlov, Plamen (Annual of Natural Sciences Department, 2022)
Currently, the conversion of megacities into smart cities is a crucial factor in improving the residents’ quality of life. The goal of the smart city concept is to develop urban management via the use of technical tools that offer the latest technologies, while taking into account applicable environmental standards, conserving resources, and achieving expected results. This article reviews and analyses various research and publications pertaining to the theoretical concepts of smart cities. Different definitions of a smart city are presented, which demonstrate how smart cities are evolving into circular and green economies.